Morphological characterization of rat incisor fluorotic lesions - Saiani, Regina Aparecida; Porto, Isabel Maria; Marcantonio Júnior, Elcio [UNESP]; Cury, Jaime Aparecido; de Sousa, Frederico Barbosa; Gerlach, Raquel Fernanda (Pergamon-Elsevier B.V. Ltd, 2009)
The morphological characterization of fluorotic rat incisor enamel was carried out. Experimental adult animals received drinking water with 45 mg F/L of fluoride, and the control group received distilled water. Fluoride concentrations found in the control and fluorosis groups were 0.04 and 0.09 mu g/mL (plasma), 0.26 and 0.66 mu g/mg (whole tibia), and 0.24 and 2.3 mu g/mg (tibia surface), with P <= 0.001 for all comparisons between the groups. A succession of white and pigmented bands was observed in the fluorotic rat incisors. Under polarizing light microscopy, cross-sections of superficial areas corresponding to the white bands (from the surface to similar to 20 mu m) showed high positive birefringence. These fluorotic lesions also exhibited the lowest resistance to superficial acid etching. No morphological differences in inner enamel were seen under scanning electron microscopy. In fluorotic enamel, only the surface layer related to the white areas presented lower birefiringence compared with the enamel of control teeth and the surface layer of the pigmented areas (normal ones) of fluorotic teeth. In conclusion, the white bands of fluorotic rat enamel represent hypomineralized superficial areas and are not subsurface lesions. The detailed description of these lesions is important to understand dental fluorosis. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Fluorosis; Polarized light microscopy; SEM; BSE-SEM; Birefringence